2022
DOI: 10.1590/0100-29452022972
|View full text |Cite
|
Sign up to set email alerts
|

Impact of some natural extracts on rooting performance of coratina olive cuttings

Abstract: Stimulating root formation is the key to successful cutting propagation. Natural root stimulators are eco-friendly, biodegradable and sustainable tools that prevent the environment from pollution. Horticulturists have given the role of sol-vents in natural extracts little attention. Therefore, the aim of this study was to study the effect of three extract solutions (aqueous, vinegary and ethanol) for ten natural extracts (humic, licorice roots, ginger roots, cinnamon bark, garlic bulbs, bread yeast, moringa le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(81 reference statements)
1
0
0
Order By: Relevance
“…This can be attributed to the presence of a growth regulator IAA, minerals and vitamins in these plant extracts. Comparable findings to those of this study demonstrated the function of licorice extract in elevating indices of root growth for Gardenia plants [8], hardwood cuttings of olive (Olea europaea L.) [24], and Coratina olive cuttings [28].…”
Section: Average Fresh Weight Of the Root System (G)supporting
confidence: 79%
“…This can be attributed to the presence of a growth regulator IAA, minerals and vitamins in these plant extracts. Comparable findings to those of this study demonstrated the function of licorice extract in elevating indices of root growth for Gardenia plants [8], hardwood cuttings of olive (Olea europaea L.) [24], and Coratina olive cuttings [28].…”
Section: Average Fresh Weight Of the Root System (G)supporting
confidence: 79%